装载机差速器的可靠性优化设计 - 王剑彬; 曾庆生 (Jixie chuandong)
This paper puts forward the reliability optimum design method of loader differential mechanism by applying the theory of reliability design and the technology of optimum design. The mathematical model of reliability optimum design is established in the paper which could be used for the design of loader differential mechanism. At last the optimum example and result analysis are given.